2015
DOI: 10.1016/j.juro.2015.03.125
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Smoking as a Risk Factor among Renal Cell Carcinoma Histological Subtypes

Abstract: Traditional understanding of smoking as a renal cell carcinoma risk factor applies to clear cell and papillary renal cell carcinoma but not the chromophobe subtype. These findings underscore distinct carcinogenic mechanisms underlying the various renal cell carcinoma subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 25 publications
3
36
0
Order By: Relevance
“…However, the prevalence of the clear cell subtype was not higher among women compared with men in our study population in Japan, which partly coincides with the result from South Korea . Studies imply potential pathways of group‐based differences in the risk for the clear cell subtype via obesity, smoking, hypertension, and end‐stage renal disease in combination with genetic factors (APOL1 gene) . Since obesity and smoking habits are far less common among Asian women compared with their counterparts in Western countries, the flat “gradient” of sex difference in the clear cell subtype seems plausible as an explanation for the discrepancy between the results obtained from Western and Asian countries.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…However, the prevalence of the clear cell subtype was not higher among women compared with men in our study population in Japan, which partly coincides with the result from South Korea . Studies imply potential pathways of group‐based differences in the risk for the clear cell subtype via obesity, smoking, hypertension, and end‐stage renal disease in combination with genetic factors (APOL1 gene) . Since obesity and smoking habits are far less common among Asian women compared with their counterparts in Western countries, the flat “gradient” of sex difference in the clear cell subtype seems plausible as an explanation for the discrepancy between the results obtained from Western and Asian countries.…”
Section: Discussionsupporting
confidence: 76%
“…Differences in female lifestyle and behavioral risks (obesity and smoking) between Western countries and Japan may underlie our observed sex difference in RCC histology of the clear cell subtype, which differs from the pattern seen in Western countries . Although the prevalence of the clear cell subtype varies across populations and regions, studies in the United States and Europe consistently suggest a higher prevalence of the clear cell subtype among women, by approximately 2% to 7% .…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…20,21 With respect to histological RCC subtype, a prospective study comparing the relationship between smoking and RCC subtypes demonstrated that active smoking was significantly more common with clear cell (23%) and papillary RCC (26%) than benign histology (14%) and chromophobe RCC (6%). 22 Individuals who are current smokers or have a history of tobacco exposure present with more aggressive forms of RCC and experience worst cancer-specific survival and overall survival. In the USA, tobacco exposure is associated with higher pathological tumor, lymph node, and metastasis classification.…”
Section: Cigarette Smokingmentioning
confidence: 99%